The Impact and Targeting of Social Infrastructure Investments : Lessons from the Nicaraguan Social - Pradhan, Menno; Rawlings, Laura B. (Washington, DC: World Bank, 2014)
The benefit incidence and impact of projects financed by the Nicaraguan Emergency Social Investment Fund are investigated using a sample of beneficiaries, a national household survey, and two distinct comparison groups. The first group is constructed on the basis of geographic proximity between similar facilities and their corresponding communities; the second is drawn from the national living standards measurement study survey sample using propensity score matching techniques. The analysis finds that the social fund investments in latrines, schools, and health posts are targeted to poor communities and households, whereas those in sewerage are targeted to the better-off. Investments in water systems are poverty-neutral. Education investments have a positive, significant impact on school outcomes regardless of the comparison group used. The results of health investments are less clear. Using one comparison group, the analysis finds that use of health clinics increased as a result of the investments; using both, it finds higher use of clinics for children under age six with diarrhea. With neither comparison group does it find improvements in health outcomes. Social fund investments in water and sanitation improve access to services but have no effect on health outcomes.